Chemical composition, antifungal and antibacterial activity of the essential oil from Baccharis latifolia (Ruiz & Pav.) Pers. (Asteraceae) from Loja, Ecuador - Malagon Aviles, O. (2012)
The essential oil of aerial parts of Baccharis latifolia (asteraceae) growing wild in Ecuador was obtained by hydrodistillation